Socio-emotional skills and cooperative learning in high school students - Encalada Alarcón, Elberta Lucila (2022)
Social-emotional skills are transcendental for the development and well-being of students. They allow the strengthening of a healthy coexistence among educational agents, and therefore the implementation of rights and duties, where not only the individual welfare but also the common good is a priority. The study presented here aims to determine the relationship between socioemotional skills and cooperative learning in secondary school students of a public educational institution in Ate, Peru. The approach used was quantitative, basic and non-experimental - transversal design, correlational level. The population included 145 students. A questionnaire and a survey technique were used to collect data. Its validation was carried out with expert judgment. For reliability, it was submitted to a pilot test with 20 students; using Cronbach's Alpha coefficient, the variables reached a value of 0.838 in socioemotional skills and 0.830 in relation to collaborative learning, presenting a strong reliability. The statistical results showed a considerable positive correlation, with a value of 0.707 of Spearman's Rho and a significance level of 0.000 < 0.05. It was concluded that, by increasing students' socioemotional skills, cooperative learning can be carried out with better skills, a space that leads to the achievement of common objectives for their own and others benefit.